Traditional Uses, Pharmacological Effects, and Molecular Mechanisms of Licorice in Potential Therapy of COVID-19 - Zhang, Qian-hui; Huang, Hao-zhou; Qiu, Min; Wu, Zhen-feng; Xin, Zhan-chang; Cai, Xin-fu; Shang, Qiang; Lin, Jun-zhi; Zhang, Ding-kun; Han, Li (Frontiers in Pharmacology, 2021)
The current Coronavirus disease 2019 (COVID-19) pandemic has become a global challenge, and although vaccines have been developed, it is expected that mild to moderate patients will control their symptoms, especially in developing countries. Licorice, not only a food additive, but also a common traditional Chinese herbal medicine, which has several pharmacological effects, such as anti-inflammation, detoxification, antibacterial, antitussive, and immunomodulatory effects, especially in respiratory diseases. Since the outbreak of COVID-19, glycyrrhizin, glycyrrhizin diamine and glycyrrhizin extract have been widely studied and used in COVID-19 clinical trials. Therefore, it is a very interesting topic to explore the material basis, pharmacological characteristics and molecular mechanism of licorice in adjuvant treatment of COVID-19. In this paper, the material basis of licorice for the prevention and treatment of COVID-19 is deeply analyzed, and there are significant differences among different components in different pharmacological mechanisms. Glycyrrhizin and glycyrrhetinic acid inhibit the synthesis of inflammatory factors and inflammatory mediators by blocking the binding of ACE 2 to virus spike protein, and exert antiviral and antibacterial effects. Immune cells are stimulated by multiple targets and pathways to interfere with the pathogenesis of COVID-19. Liquiritin can prevent and cure COVID-19 by simulating type I interferon. It is suggested that licorice can exert its therapeutic advantage through multi-components and multi-targets. To sum up, licorice has the potential to adjuvant prevent and treat COVID-19. It not only plays a significant role in anti-inflammation and anti-ACE-2, but also significantly improves the clinical symptoms of fever, dry cough and shortness of breath, suggesting that licorice is expected to be a candidate drug for adjuvant treatment of patients with early / mild COVID-19.